From invasive species to agricultural resource: evaluation of Phragmites australis from Zarivar Lake as an organic amendment for the release of phosphorus, potassium, micronutrients and toxic metals - Shno Karimi; Zahra Kolahchi; Mahboube Zarrabi; Safoora Nahidan; Taqi Raza (Discover Applied Sciences)
Abstract Overgrowth of Phragmites australis has become a serious issue for Zarivar Lakes and many water bodies worldwide. The objective of this research was to use the harvested common reed as a soil organic amendment. For this purpose, the release kinetics of phosphorus and potassium from Phragmites a. biomass were studied. This study was conducted as a split-plot design with two treatments including a control and 3% (w/w) Phragmites a. and eight incubation durations (7, 14, 28, 42, 56, 70, 84, 98 days) in a fully randomized design with three replications. After 98 days, the amount of cumulative phosphorus released increased from 12.4 to 127.3 mg/kg in the control treatment and from 18.9 to 150.1 mg/kg in the 3% (w/w) treatment, while potassium released increased from 269.6 to 2206.1 mg/kg in the control treatment and from 322.2 to 2584.3 mg/kg in the 3% treatment. The release intensity (b) of phosphorus was larger than that of potassium in the exponential equation, and the release of the elements was a diffusion function in the parabolic equation. In the Phragmites a., dominant functional groups (C-H) and (C = O) were reported. The surface of the plant was smooth and dense. The results showed that the Phragmites a. can be a source of phosphorus and potassium and does not cause heavy metal pollution to the soil and exponential and parabolic equations had the highest correlation with the release of elements. Phragmites a. can be used as an environment-friendly organic amendment, however, additional research is needed.